Influence of Quenching Media and Holding Time on Hardness and Microstructure of AISI 1045 - Tama, Bayu Widias; Rosidah, Afira Ainur (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) - ITP, 2024)
AISI 1045 material is carbon steel which is widely used in the industrial world as a material for making gears, bolts, and axles, however, in its use AISI 1045 steel has shortcomings in its hardness value. When used, AISI 1045 steel must be hardened through a hardening heat treatment process so that it is more capable of being used. It is important to carry out the hardening process so that the material has greater hardness, this property is related to wear resistance. This research was carried out with the aim of analyzing the effect of variations in holding time and variations in cooling media on the hardness and microstructure of AISI 1045 Steel. The heating temperature used was 840⁰C with a holding time of 17 and 22 minutes using air, oil, and grease cooling media. The method used to measure hardness in this research is the Brinell hardness method. The results of the research showed changes in the microstructure from initially ferrite and pearlite to bainite and martensite, the highest hardness was obtained in the specimen with oil quench media with a holding time of 17 minutes with a value of 643.35 kgf/mm2 and the lowest hardness value was obtained in the specimen with quench media air with a holding time of 22 minutes with a value of 153.44 kgf/mm2.